KEDUDUKAN BENDAHARA PASCA BERLAKUNYA UNDANG - UNDANG NOMOR 1 TAHUN 2004 TENTANG PERBENDAHARAAN NEGARA - Febie Saputra (Yuridika, 2015)
Compared with previous laws, law No. 17 of 2003 concerning state finance has some fundamental differences and new matters, such as the post of treasurer as functional position. It shows that it is important that finance management must be managed by functional position as stated in a Article 10 paragraph (3) of Law No. 1 of 2004. Thus, the embodiment of treasurer as functional position must be implemented immediately so that the clear and ideal position and the responsibilities can be realized and cannot be separated from the government role in implementing good governance in state budget since state budget is a form of state financial management that must be transparent and accountable for citizen's prosperity as it provided in UUD NKRI 1945. Therefore, the ideal implementation of state budget for prosperity of people is the embodiment of the government efforts for public interest without any distinction on Indonesian social plurality.